2012
DOI: 10.1002/asia.201101006
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Tellurium Nanomaterials

Abstract: We prepared four differently shaped Te nanomaterials (NMs) as antibacterial reagents against Escherichia coli. By controlling the concentrations of hydrazine (N2H4) as reducing agent, NaCl, and temperature, we prepared Te nanowires, nanopencils, nanorices, and nanocubes. These four Te NMs resulted in a live/dead ratio of E. coli cells of less than 0.1, which is smaller than that of Ag nanoparticles. The order of antibacterial activity against E. coli is nanocubes ≈ nanorices > nanopencils ≈ nanowires. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 66 publications
(69 reference statements)
0
40
0
Order By: Relevance
“…It was recently reported that chemically synthesized TeNSs display efficient antibacterial properties against E. coli, which seem to be even better than those exhibited by silver NSs (14). Given that Ag nanoparticles are nowadays considered the NSs exhibiting the most effective antimicrobial properties (15), this study opened brand new and promising perspectives for TeNS applications.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…It was recently reported that chemically synthesized TeNSs display efficient antibacterial properties against E. coli, which seem to be even better than those exhibited by silver NSs (14). Given that Ag nanoparticles are nowadays considered the NSs exhibiting the most effective antimicrobial properties (15), this study opened brand new and promising perspectives for TeNS applications.…”
mentioning
confidence: 79%
“…Pores increase the surface area-to-volume ratio of the NSs, since a greater fraction of atoms is located at the surface and leads to increased chemical reactivity of the NSs (36). We decided to test the chemical reactivity of the TeNSs as an antibacterial agent since it was recently shown that chemically synthesized tellurium NSs showed very promising antibacterial properties against E. coli, comparable to or higher than those to silver NSs (14). The same antibacterial properties were then reported using Te nanostructures against S. aureus, P. aeruginosa, Salmonella enterica serovar Typhi, and Klebsiella pneumoniae (37).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zare et al (25) have reported that the Te NRs can completely inhibit the growth of C. albicans at concentrations of ≥ 2000 μg.mL -1 through inhibition of the squalene monooxygenase gene expression. In addition, Lin et al (26) reported that diff erent Te nanomaterials such as nanowires (20 nm diameter by 880 nm length), nanopencils (70 nm diameter by 440 nm length), nanorices (50 nm diameter by 130 nm length), and nanocubes (80 nm) which were prepared by the chemical reduction of tellurium dioxide by hydrazine represented a higher antibacterial activity against E. coli compared to Ag nanoparticles that are commonly used as antibacterial reagents. They also reported that the antibacterial eff ect of nanocubes and nanorices are approximately equal and their antibacterial eff ect is higher than nanopencils and nanowires (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lin et al (26) reported that diff erent Te nanomaterials such as nanowires (20 nm diameter by 880 nm length), nanopencils (70 nm diameter by 440 nm length), nanorices (50 nm diameter by 130 nm length), and nanocubes (80 nm) which were prepared by the chemical reduction of tellurium dioxide by hydrazine represented a higher antibacterial activity against E. coli compared to Ag nanoparticles that are commonly used as antibacterial reagents. They also reported that the antibacterial eff ect of nanocubes and nanorices are approximately equal and their antibacterial eff ect is higher than nanopencils and nanowires (26). It seems that the higher size of Te nanomaterials, the lower antibacterial activity could be observed (26).…”
Section: Discussionmentioning
confidence: 99%
“…Besides silver nanoparticles, other metal nanomaterials have also been studied for antimicrobial treatment, including gold [47], copper [48,49], tellurium [50,51], and bismuth [52]. Moreover, many studies have revealed the antibacterial activity of metal oxide nanomaterials, such as zinc oxide (ZnO) [53], copper oxide (CuO) [54,55], magnesium oxide (MgO), nitric oxide (NO) [56], titanium dioxide (TiO 2 ) [57], aluminum oxide (Al 2 O 3 ) [58], magnetic iron oxide (α-Fe 2 O 3 ) [59], and cerium oxide (CeO 2 ) [60] nanoparticles.…”
Section: Nanomaterials As Active Antibacterial Agentsmentioning
confidence: 99%